THE NEED FOR ASSESSING TECHNOLOGY DEPLOYMENT IN ENERGY SYSTEMS MODELS TO DECARBONISE THE RESIDENTIAL SECTOR: A SYSTEMATIC LITERATURE REVIEW (Alimentos Ciencia e Ingeniería, 2020)
Scientists across the world are working on understanding the potential impact of buildings’ energy consumption on climate change and vice versa. Buildings comprise between 20% and 40% of overall energy consumption depending on the economic development, cultural, and geographical features of a country or region; heating and cooling can represent up to 80% of the total energy consumed in buildings. Energy systems models (ESMs) have emerged to help the research community to build logical scenarios and simulate the complexity of energy sectors of the global economy. However, current challenges must still be included in ESMs, especially challenges from the end-use energy sectors (i.e. transport, industry, and buildings). This research review assesses two of these current challenges in modelling the energy transition of the residential building sector (RBS): 1. the consideration of the residential sector in energy systems models, and 2. the available technologies to decarbonise the sector.